Identifying incident oral and pharyngeal cancer cases using Medicare claims - Mahnken Jonathan D; Keighley John D; Girod Douglas A; Chen Xueyi; Mayo Matthew S (BMC, 2013)
Abstract Background Baseline and trend data for oral and pharyngeal cancer incidence is limited. A new algorithm was derived using the Surveillance, Epidemiology, and End Results (SEER)-Medicare linked database to create an algorithm to identify incident cases of oral and pharyngeal cancer using Medicare claims. Methods Using a split-sample approach, Medicare claims' procedure and diagnosis codes were used to generate a new algorithm to identify oral and pharyngeal cancer cases and validate its operating characteristics. Results The algorithm had high sensitivity (95%) and specificity (97%), which varied little by age group, sex, and race and ethnicity. Conclusion Examples of the utility of this algorithm and its operating characteristics include using it to derive baseline and trend estimates of oral and pharyngeal cancer incidence. Such measures could be used to provide incidence estimates where they are lacking or to serve as comparator estimates for tumor registries.